Bromhexine inhibits SARS-CoV-2 Omicron and variant pseudovirus infection via ACE2-targeted mechanisms - Zúñiga, Rafael; Venturini, Whitney; González, Natalia; Valenzuela-Hormazábal, Paulina; Sánchez-Aros, Laura; Ramírez, David; Cayo, Angel; Vilos, Cristian; Zúñiga, Leandro (Frontiers in Pharmacology, 2026)
BackgroundSevere acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes a highly infectious disease characterized by fever, acute respiratory illness, and pneumonia, known as coronavirus disease 2019 (COVID‐19). SARS‐CoV‐2 infects host cells through the interaction of its spike glycoprotein (S protein) with human angiotensin‐converting enzyme 2 (hACE2). Structural studies have shown that hACE2 interacts exclusively with the receptor‐binding domain (RBD) of the spike. A high binding affinity between spike and hACE2 has been linked to increased viral infection. Disrupting this interaction can reduce viral infectivity.MethodsThis study aimed to assess infection using Omicron variant pseudovirus in a stable HEK‐293 cell line expressing hACE2 (HEK‐293/ACE2), treated with bromhexine hydrochloride. First, immunofluorescence and Western blot confirmed the presence of hACE2 in the stable line. Then, bromhexine concentrations for treatment were determined by cytotoxicity assays. Next, infection was evaluated using Omicron pseudoviruses carrying GFP and luciferase reporter genes. Infection levels were measured through fluorescence or luciferase activity.ResultsBromhexine reduced infection with an IC50 of 17.3 ± 0.9 μM. About 40% inhibition was also observed against Alpha, Beta, and Delta variants at 40 μM. Computational docking followed by molecular dynamics simulations showed that bromhexine binds to the extracellular domain of hACE2, with recurrent contacts near Phe40, Phe390, and Asn394.ConclusionConsistent with this model, our findings support an entry‐inhibition mechanism whereby bromhexine destabilizes the SARS‐CoV‐2 spike–ACE2 interface, preventing viral entry. Overall, these results suggest bromhexine as a potential repurposing candidate and support its inclusion in therapeutic strategies aimed at both current and emerging SARS‐CoV‐2 variants.